2019
DOI: 10.1111/jfbc.12793
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone attenuates phosphorylation of AKT to inhibit kidney cancer cell proliferation

Abstract: Thymoquinone (Tq) is an active compound from Nigella sativa which is used in traditional medicine. The effect of Tq on kidney cancer and the pathway of action remain unproven. Herein, we report the anticancer properties of Tq on kidney cancer cells. Tq demonstrated anti‐proliferative effects in A498 cells with a GI50 value of 40.07 µM and Caki‐1 cells with a GI50 of 51.04 µM by the MTT assay. Tq exhibited nuclear fragmentation and inhibited trans‐endothelial migration of A498 and Caki‐1 cells in a dose‐respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…6 Additional, thymoquinone is a lipophilic molecule that is capable to prevent LP via Fenton reaction. 19 Gani et al indicated that extract of NS diminished hepatic enzymes and LP, which is in line with the outcomes of the existing study. 20 Accordingly, it appears that thymoquinone with its antioxidant properties could condense LP and increase TAC in the treatment groups via inhibiting the construction of ROS.…”
Section: Discussionsupporting
confidence: 81%
“…6 Additional, thymoquinone is a lipophilic molecule that is capable to prevent LP via Fenton reaction. 19 Gani et al indicated that extract of NS diminished hepatic enzymes and LP, which is in line with the outcomes of the existing study. 20 Accordingly, it appears that thymoquinone with its antioxidant properties could condense LP and increase TAC in the treatment groups via inhibiting the construction of ROS.…”
Section: Discussionsupporting
confidence: 81%
“…Thymoquinone (Tq) is one such active ingredient of Black Caraway seed ( Nigella Sativa ), which is widely used in traditional medicine of the Middle East (Padhye, Banerjee, Ahmad, Mohammad, & Sarkar, 2008). Tq has been proven to be effective against various types of cancer, including kidney, ovarian, colon, and breast cancer (Dera & Prasanna, 2019). The compound exhibits antioxidant and anti‐inflammatory properties (Gali‐Muhtasib, Roessner, & Schneider‐stock, 2006), and has been shown to prevent myocardial and perivascular fibrosis induced by lipopolysaccharide in rats (Asgharzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sativa, which is extensively used for centuries in traditional medicine of the Middle East (Padhye, Banerjee, Ahmad, Mohammad, & Sarkar, 2008). Evidence for the therapeutic potential of Tq has been shown in many cancer types, like kidney, ovarian, colon, and breast (Ayed & Prasanna, 2019). Tq was studied for its preventive effects in myocardial, perivascular fibrosis (Asgharzadeh et al, 2018), and systemic infections (Khan et al, 2018).…”
Section: Thymoquinone (Tq) Is An Active Component Isolated From Nigellamentioning
confidence: 99%